2021
DOI: 10.1136/jitc-2020-001642
|View full text |Cite
|
Sign up to set email alerts
|

Biologic subtypes of melanoma predict survival benefit of combination anti-PD1+anti-CTLA4 immune checkpoint inhibitors versus anti-PD1 monotherapy

Abstract: PurposeAnti-programmed cell death protein 1 (PD1)±anti-cytotoxic T-lymphocyte associated protein 4 (CTLA4) immune checkpoint inhibitors (ICIs) are standard therapeutic options for metastatic melanoma. We assessed whether biologic subtype according to primary tumor type or genomic subtype can function as predictive biomarkers for anti-PD1±anti-CTLA4 ICI in patients with advanced melanoma.MethodsWe performed a single-center retrospective cohort analysis of patients who received anti-PD1±anti-CTLA4 ICI for advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…The combination of nivolumab and ipilimumab revealed superiority with a 5-year survival of 52% [23]. Especially for NRAS, mutant melanoma combination therapy is essential [61]. Patients with metastases to the brain also benefitted from the combination therapy, with an intracranial response in 46% of patients who received the combination and 20% intracranial response rate for the single agent nivolumab, irrespective of their mutational status [59,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of nivolumab and ipilimumab revealed superiority with a 5-year survival of 52% [23]. Especially for NRAS, mutant melanoma combination therapy is essential [61]. Patients with metastases to the brain also benefitted from the combination therapy, with an intracranial response in 46% of patients who received the combination and 20% intracranial response rate for the single agent nivolumab, irrespective of their mutational status [59,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this study was that genomic profiling was not available for all patients. We have previously established that the presence of oncogenic driver mutations can predict ICI response in cutaneous melanoma [ 46 ]. However, due to the smaller sample size and missing genomic data—we could not assess the relationship between genomic driver mutations and ICI response in this cohort of mUM patients.…”
Section: Discussionmentioning
confidence: 99%
“…In another recent retrospective study, Rose and colleagues showed significantly improved PFS and OS in NRAS mut melanoma patients treated with anti-PD1 + anti-CTLA4 cotherapy (HR 0.34, 95% CI 0.16 to 0.71 and HR 0.24, 95% CI 0.10 to 0.62) in comparison to anti-PD1 monotherapy. Therefore, the NRAS mutational status has been suggested as a biomarker for an immunotherapeutic regimen [60].…”
Section: Current Clinical Treatmentsmentioning
confidence: 99%